2023
DOI: 10.3390/polym15051082
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Scaffolds Used in Dental Pulp Regeneration by Tissue Engineering Approach

Abstract: Currently, the challenge in dentistry is to revitalize dental pulp by utilizing tissue engineering technology; thus, a biomaterial is needed to facilitate the process. One of the three essential elements in tissue engineering technology is a scaffold. A scaffold acts as a three-dimensional (3D) framework that provides structural and biological support and creates a good environment for cell activation, communication between cells, and inducing cell organization. Therefore, the selection of a scaffold represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Hybrid scaffolds, which combined natural and synthetic materials, emerged as a promising approach. These scaffolds offered the biocompatibility and biodegradability of natural materials with the tunable properties of synthetic polymers [18,19].…”
Section: Mid-2000smentioning
confidence: 99%
“…Hybrid scaffolds, which combined natural and synthetic materials, emerged as a promising approach. These scaffolds offered the biocompatibility and biodegradability of natural materials with the tunable properties of synthetic polymers [18,19].…”
Section: Mid-2000smentioning
confidence: 99%
“…It was demonstrated that tooth fragments filled with these nanofibers produced pulp-like tissue in vivo. In dentistry, this type of scaffold, in MN/MN patch presentation, could aid regeneration beyond the pulp revascularization [ 75 ].…”
Section: Materials Used For Hydrogel-forming Microneedles: Fabricatio...mentioning
confidence: 99%
“…Among other aspects, this reduces the morbidity of other treatments, such as surgery. The availability of biomaterials with an appropriate physical structure, adhesion potential, and cell proliferation, plays an influential role in the regeneration and repair of bone tissue [9][10][11], with a crucial factor being the advanced state of knowledge on stem cells [12][13][14] and on the growth factors that favor the differentiation and acceleration of these processes [15,16]. 2 Given the scarce bioavailability of autologous grafts, the low osteoinductive capacity of xenografts appears to be the ideal solution.…”
Section: Introductionmentioning
confidence: 99%